Materials and Construction of Transparent Cover of Formwork for Heat Treatment of Concrete with Employment of Solar Energy - D. Koroteev, Dmitry; Kharun, Makhmud; A. Stashevskaya, Nadezhda; ., . (International Journal of Engineering and Technology, 2018)
Heat treatment of concrete is one of the operations during manufacturing of concrete elements at the plants. It allows speeding up the process of concrete curing and getting complete product in a short time. Concrete is heated under the temperature, which can be obtained in solar energy equipment. It allows replacing fossil fuels by solar energy partly or completely and reducing costs for manufacturing of concrete elements. The efficiency of employment of solar energy depends on materials and construction of the solar energy equipment. The object of research is formwork, equipped by transparent cover, which is a simple type of the solar energy equipment. The research work is devoted to determination of optimal material and number of layers of transparent cover. The obtained results allow increasing efficiency of employment of solar energy for heat treatment of concrete and reducing costs for manufacturing of the solar energy equipment.Â Â